Optimalisasi Peran Peer-To-Peer Lending Syariah dalam Meningkatkan Kesejahteraan UMKM di Kabupaten Probolinggo: Pendekatan Inklusif di Era Digital - Rahmah, Maulidatur; Billah, Zahida I’tisoma; Arifin, Moh. Samsul (Universitas Batanghari Jambi, 2025)
The development of Islamic financial technology has opened new opportunities to support the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in Probolinggo Regency. One rapidly growing instrument is Sharia Peer-to-Peer (P2P) Lending, which offers interest-free financing access through digital platforms. This study aims to analyze the role, challenges, and optimization strategies of Sharia P2P Lending in improving MSME welfare through an inclusive approach in the digital era. The approach used is qualitative descriptive-explorative, with data collection techniques including in-depth interviews, observations, and documentation. Informants consist of MSME actors, Sharia P2P lending platform managers, the Office of Cooperatives and MSMEs, and Islamic financial institutions in Probolinggo Regency. The research findings show that Sharia P2P Lending plays a significant role in expanding financing access, especially in terms of contract flexibility, simplified procedures, and compliance with sharia principles. However, its implementation still faces challenges such as low financial and digital literacy, limited outreach, and inadequate technological infrastructure. Optimal implementation has proven to enhance the production capacity, marketing, and economic welfare of MSME actors. This study offers strategic contributions through proposals to strengthen digital literacy and regulatory support as a foundation for inclusive and sustainable growth of Sharia P2P Lending. Future research is recommended to explore risk mitigation models in Sharia P2P Lending and the role of local institutions and communities in expanding its impact on MSME economic empowerment.